Lycosa Latreille, 1804 (Araneae, Lycosidae) of Israel, with a note on Geolycosa Montgomery, 1904 - Armiach Steinpress, Igor; Cohen, Mira; Pétillon, Julien; Chipman, Ariel D.; Gavish-Regev, Efrat (European Journal of Taxonomy, 2022)
Lycosa (Araneae, Lycosidae) is a wolf spider genus typical of subtropical latitudes in the western Palearctic. Despite being erected over 200 years ago, the taxonomy of Lycosa is still unclear. Many species formerly ascribed to it are currently being moved to other genera, while new species are still being described. The species of Lycosa of the western Mediterranean basin are relatively well known, yet the Levantine region, the easternmost part of the Mediterranean basin, has not received much attention since the early 20th century. Here, we study Lycosa from the southern Levant using morphological, molecular and behavioral characteristics, to delimit the species found in this region. We describe two new species: L. hyraculus sp. nov. and L. gesserit sp. nov. We re-describe the widespread and polymorphic species, Lycosa piochardi Simon, 1876. Lycosa piochardi infraclara Strand, 1913 is synonymized with Lycosa piochardi. By adding novel data to the molecular phylogeny of Lycosa created by Planas et al. (2013) and re-analyzing it, we explore the relationship of the Levantine species to other Mediterranean species of Lycosa. We discuss habitat preferences of the two species of Lycosa. Additionally, we report the burrowing species Geolycosa vultuosa (C.L. Koch, 1838) as a new record to Israel, thus extending the distribution of this species and genus into the Levant.